Population divergence and structure of Cirrhinus mrigala from peninsular rivers of India, revealed by mitochondrial cytochrome b gene and truss morphometric analysis. (April 2014) - Das, Sofia Priyadarsani; Bej, Dillip; Swain, Subrat; Mishra, Chandra Kanta; Sahoo, Lakshman; Jena, Joykrushna; Jayasankar, Pallipuram; Das, Paramananda
Abstract Genetic diversity and population structure of Cirrhinus mrigala from peninsular riverine systems of India was studied using mitochondrial DNA gene, cytochrome b and truss morphometric analysis. Analysis of 982 bp of the cytochrome b gene from 182 samples collected from six rivers revealed the presence of 28 haplotypes with overall high haplotype diversity value of 0.78981 and nucleotide diversity value of 0.00215. Analysis of molecular variance (AMOVA) showed that genetic variation is mainly harbored within populations rather than among populations. The pairwise Fst values (−0.009 to 0.084) was indicative of a low genetic structure among mrigal populations. Morphometric examination of 243 samples using 10 truss landmarks and principal component analysis showed a similar trend when compared with genetic data. Overall, low genetic and morphometric differences were observed despite those populations from different geographic locations. The results of this study would provide essential information to resource recovery and help in delineating populations for fishery management. Besides, the data will provide a valuable baseline for further investigations on the geographic distribution of this commercially important fish species.